المقاصد القرآنية عند الإمام الصابوني في تفسيره صفوة التفاسير: المقاصد الخاصة عند الإمام الصابوني - جاسم، إلهام رفعت; الكيلاني، حيدر عبدالعزيز إسماعيل حمد (الجامعة المستنصرية - كلية التربية الأساسية, 2023)
تناول في هذا البحث موضوع (المقاصد القرآنية عند الإمام الصابوني في تفسيره صفوة التفاسير) (المقاصد الخاصة) والذي تمثل بمبحثين ومقدمة. فتعرضنا في المبحث الأول عن العقائد عند الصابوني في تفسيره صفوة التفاسير وكان من خمسة مطالب المطلب الأول (تصحيح التصورات والعقائد) أما المطلب الثاني فتحدثت به عن (تزكية النفس البشرية) والمطلب الثالث تكلمت فيه عن (إقامة العدل بين الناس) والمطلب الرابع فكان حول (الحرية) والمطلب الخامس حول (رفع الحرج) أما المبحث الثاني فتكلمنا فيه عن الأخلاق عند الصابوني في تفسيره صفوة التفاسير وتكون من خمسة مطالب المطلب الأول كان عن (تقرير كرامة الإنسان) والمطلب الثاني عن (تقرير حقوق الإنسان) أما المطالب الثالث فتحدثت به عن (تكوين الأسرة الصالحة) والمطلب الرابع عن (انصاف المرأة وتحريرها من ظلم الجاهلية) والمطلب الخامس تحدث به عن (بناء الأمة الشهيدة على الناس) ثم الخاتمة وتليها المصادر والمراجع. In this research, we have dealt with the subject of (the Quranic purposes of Imam Al-Sabouni in his interpretation of the elite of interpretations) (special purposes), which is represented by two topics and an introduction. In the first topic, we dealt with the beliefs of al-Sabouni in his interpretation of the elite of interpretations, and it consisted of five demands. And the fourth demand was about (freedom) and the fifth demand was about (reducing embarrassment). As for the second topic, we talked about ethics according to Al-Sabouni in his interpretation, Safwat al-Tafseer, and it consisted of five demands. The first demand was about (determination of human dignity) and the second demand was about (reporting human rights). The third, I talked about (forming a good family), the fourth requirement, about (justice for women and their liberation from the oppression of the Jahiliyyah), and the fifth requirement, he spoke about (building the martyr nation on people), then the conclusion, followed by the references sources.
Keywords: القرآن الكريم -- الصابوني، إسماعيل بن عبدالرحمن، ت. 449 م. -- علم التفسير -- المقاصد القرآنية